IgA nephropathy and hodgkin’s disease: a rare coincidence : case report and literature review - Bergmann, Jörg Stefan; Buchheidt, Dieter; Waldherr, Rüdiger; Maywald, Ole; Woude, Fokko J. van der; Hehlmann, Rüdiger; Braun, Claude (American journal of kidney diseases, 2005)
In Hodgkin’s disease, the most common paraneoplastic glomerular abnormality is minimal change nephropathy, although other glomerular diseases occasionally have been described. We report a case of extracapillary immunoglobulin A glomerulonephritis presenting as acute renal failure in a woman with newly diagnosed Hodgkin’s disease. Treatment with the bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone regimen resulted in complete hematologic and renal remission for more than 1 year after diagnosis.